2011
DOI: 10.1016/j.jvoice.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Voice-Related Complaints in the Pediatric Population

Abstract: Subjective evaluation of the voice by the patient is routinely assessed in the adult dysphonic population; this is, however, not the case in the pediatric population. There were three objectives of this study: the first goal was to study the ability of children aged 5-13 years to express themselves about physical, emotional, and sociofunctional aspects of their voice. The second goal was to explore if specific voice-related complaints were expressed by dysphonic children as compared with normophonic children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
1
33
1
8
Order By: Relevance
“…Parents of children and adolescents can measure the impact of voice disorder on their children's quality of life using the PVRQoL survey (6) -a valid instrument composed of ten questions divided into two domains: physical and socio-emotional that can sensitively identify the impact of vocal alteration (5) . Research has reported that children without voice disorders present PVRQoL scores close to 100 (17) -not showing negative impact on quality of life, whereas children with laryngeal alterations present reduced scores for all domains compared with those of children without laryngeal and vocal alterations, demonstrating that vocal deviation interferes with quality of life (17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of children and adolescents can measure the impact of voice disorder on their children's quality of life using the PVRQoL survey (6) -a valid instrument composed of ten questions divided into two domains: physical and socio-emotional that can sensitively identify the impact of vocal alteration (5) . Research has reported that children without voice disorders present PVRQoL scores close to 100 (17) -not showing negative impact on quality of life, whereas children with laryngeal alterations present reduced scores for all domains compared with those of children without laryngeal and vocal alterations, demonstrating that vocal deviation interferes with quality of life (17) .…”
Section: Discussionmentioning
confidence: 99%
“…The specific scientific literature describes three parental assessment tools related to the voice, namely: Pediatric Voice Outcome Survey (PVOS), Pediatric Voice Handicap Index (PVHI), and Pediatric Voice-related Quality-of-Life (PVRQoL) protocol (5) . The use of voice assessment tools applied to parents of children and adolescents is important because they have the ability to understand the context of the problem and, from this perception, seek specialized assistance for their children (6) .…”
Section: Introductionmentioning
confidence: 99%
“…32 In the child form, the items address the child himself or herself (for example: ''Do you have to strain when you speak? ''); in the parent form, the items duplicate those used in the child form but address the parents (for example: ''Do your child strain when he/she speaks?…”
Section: Methodsmentioning
confidence: 99%
“…However, two recent studies where focused group interviews were conducted with dysphonic children and their parents show that children are both conscious of and affected by their vocal symptoms and that they are capable of describing them accurately without adult help already from the age of 5 years. 31,32 The studies also found evidence that the parental evaluation of the child's difficulties is not in full concordance with the child's own evaluation. The validity of the parental proxies in the three existing voice-related child questionnaires has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The parental assessment protocols have been highly recommended in the pediatric voice clinic, since the young age of the patient can derail the vocal self-assessment (1) . Among the parental assessment procedures, we highlight the quality of life related to voice, enabling better targeting of therapeutic procedures (2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%